Small and medium entrepreneurs in Southeast Asia - Clapham, Ronald 1935- (Institute of Southeast Asian Studies, 1985)
This study investigates the activities of small and medium entrepreneurs in the manufacturing sector in South and Southeast Asia, to examine their actual and potential contribution to social and economic development in their countries. The factors that encourage or hinder this contribution are also identified and suggestions are put forward on how the contribution towards development can be rendered more effective